Does the postcoital test predict pregnancy in WHO II anovulatory women? A prospective cohort study. (April 2016) - Nahuis, Marleen J.; Weiss, Nienke S.; Van der Velde, Minke; Oosterhuis, Jur J.E.; Hompes, Peter G.A.; Kaaijk, Eugenie M.; van der Palen, Job; van der Veen, Fulco; Mol, Ben Willem J.; van Wely, Madelon
Abstract: Objective: To assess the capacity of the postcoital test (PCT) to predict pregnancy in WHO II anovulatory women who are ovulatory on clomiphene citrate (CC). In these women, an abnormal PCT result could be associated with lower pregnancy chances, but this has never been proven or refuted. Study design: Prospective cohort study was performed between December 2009 and September 2012 for all women who started ovulation induction with CC in one university clinic and two teaching hospitals in the Netherlands. A PCT was performed in one of the first three ovulatory cycles. Ovulation induction with CC was continued for at least six cycles. The PCT was judged to be positive if at least one progressive motile spermatozo was seen in one of five high power fields at 400× magnification. The primary outcome was time to ongoing pregnancy, within six ovulatory cycles. Results: In 152 women the PCT was performed. 135 women had a reliable, well-timed PCT. The ongoing pregnancy rate was 44/107 (41%) for a positive and 10/28 (36%) for a negative PCT. The hazard rate for ongoing pregnancy was 1.3 (95% CI 0.64–2.5) for a positive versus a negative PCT. Thirty five of 77 (46%) women with clear mucus had an ongoing pregnancy versus 12 of 45 (27%) women in whom the mucus was not clear (HR 2.0; 95% CI 1.02–3.84, p  = 0.04). Conclusion: The present study suggests that the outcome of the postcoital test in women with WHO-II anovulation that undergo ovulation induction with CC does not have a large effect on ongoing pregnancy chances over time.